Importancia del Fósforo en el incremento de la producción, en cultivos de ciclo corto - Herrera Méndez, Mercedes del Pilar (2020)
This document indicates the importance of phosphorus in increasing production in short cycle crops, as an essential nutrient for the nutrition of soils, which affects the development and production of the plantation. Most of the producers are dedicated to the production of short cycle crops because it allows them to obtain profitability in short periods of time, however, the yields are not those expected due to lack of adequate management of the crop, among which the use of resistant or hybrid varieties (depending on the crop), lack of technification of the terrain, little irrigation, poor use of nutrients and lack of integrated pest management. Based on the information gathered, it was concluded that the organic phosphorus in the soil can be associated with the organic matter of that soil (humus) or with the recently contributed organic debris from plants or animals, which is used by the roots of the plants or that they can intervene in the same reactions as other phosphate ions present in fertilizers; an adequate phosphorus supplement in our crops with the aim of promoting plant growth and helping them to reproduce optimally. Thus, a plant with the correct amount of phosphorus will grow vigorously and mature earlier than other plants that lack it; Like nitrogen, phosphorus is a very important growth factor and, in addition, root development is favored by a correct contribution of this nutrient at the beginning of the vegetative cycle, which is why its knowledge is of vital importance when we propose a new plantation regardless of the type it is and phosphorus is a precocity factor, since it activates the initial development and tends to shorten the vegetative cycle, favoring maturation. Therefore, it is important for early crops and those located on the northern limit of its geographical area (corn). Likewise, it increases the resistance of the plant to cold and diseases, like potassium, it is well known that the application of phosphorus via foliar stimulates the generation of phytoalexins that act as a defense for plants against attacks by fungi or bacteria.